Signal technique for friend or foe detection of intelligent malicious user in cognitive radio network. (20th August 2019) - Sabuj, Saifur Rahman; Hamamura, Masanori
In cognitive radio networks, security issues arise when intelligent malicious users can attack and decrease the permitted channel for unlicensed users (secondary users). In this paper, we propose a novel scheme, based on friend or foe (FoF) detection technique with physical layer network coding, to enable discrimination between secondary users and intelligent malicious users. Theoretical expressions are derived for probabilities of detection of secondary user, miss detection, and false alarm. In addition, the effectiveness of the proposed approach is evaluated by theoretical analysis and Monte Carlo simulation. Furthermore, an algorithm is proposed for distinguishing between secondary user and intelligent malicious user. Finally, based on the outcome of simulation of probabilities and normalised cross-correlation, it is determined that the proposed scheme outperforms in terms of orthogonal frequency-division multiplexing (OFDM) signal compared with quadrature phase-shift keying (QPSK) signal over cognitive radio network.